Pengaruh Merger Bank Syariah BUMN Terhadap Minat Menabung Di BSI Pada Masyarakat Solo Raya - Agus Setiawan; Erie Dwi Cahya; Yesi Asandi Salsabila (Lisyabab : Jurnal Studi Islam dan Sosial, 2022)
This study aims to determine how much influence the Merger of Bank Syariah Indonesia has on attitudes, subjective norms, behavioral control and behavioral intentions on the interest in saving in the people of Solo Raya. This type of research is quantitative research. The population is 123 respondents from the Solo Raya community and a sample of 30 respondents. While the data collection technique used in this study was a questionnaire. The data analysis used is the classical assumption test, simple and multiple linear regression analysis, and hypothesis testing. The results showed that the behavioral attitude variable had a partial effect on intention by 0.275, the subjective norm variable had an effect on intention by 0.485, the behavioral control variable had an effect on intention by 0.228. Behavioral attitudes, subjective norms, behavioral control, and behavioral intentions partially influence interest. The results show that the intention factor has the biggest factor encouraging people's interest in saving at Islamic banks, intention factors such as economic benefits in this case for the results obtained by the community from saving at Indonesian Islamic banks.